Editorial: Technologies in smallholder poultry development: characterization, utilization, conservation, and improvement - Yakubu, A.; Bamidele, Oladeji; Thiruvenkadan, A.K.; Okpeku, M.; Çelik, S. (Frontiers Media, 2023)
Smallholder poultry production accounts for about 80% of the poultry flock in low- and middle-income countries. The birds play important roles in rural livelihoods, food security, household income, culinary and traditional medicine and strengthening of social relationships (Li et al., 2020; Bamidele and Amole, 2021; OchoraKasima et al., 2023). Despite the benefits derived from Smallholder poultry production systems (SPPS), the production as well as the productivity is low. The low performance of the birds could be attributed mainly to low genetic potential, genetic erosion occasioned by indiscriminate crossbreeding, poor nutrition, health and housing and vagaries of climatic factors (Samaraweera et al., 2021; Birhanu et al., 2021; Wilson et al., 2022). This, according to Birhanu et al. (2023), necessitates poultry research and development using innovative and technological approaches in genetics, feed supply, health services, housing, and public-private partnership to deliver integrated innovation packages. The outcome will not only boost production, but ensure increased productivity and profitability of the SPSS.